Information, communication, and space technology - Razani, Mohammad
Information, Communication, and Space Technology provides a novel illustration of that connection. Dividing content into sections that cover ICT, existing and future space technologies, and satellites, the author demonstrates the individual and combined power of each of these parts of the overall system. He explores how the combination of concepts from each of these interrelated fields is creating massive potential for broader advances in areas such as robotics, communications, navigation, agriculture, health care, and nanotechnology. The book introduces particular potential innovations, including "rocket-less" spacecraft launches, and development of a global system to balance energy distribution by using satellites that would collect solar energy and transmit it via microwave beams to different locations around the world.